2020
DOI: 10.1088/1742-6596/1712/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Optimising e-commerce customer satisfaction with machine learning

Abstract: Customer insighs is the key to the success of e-commerce. Therefore, factors affecting customer satisfaction leading to product purchase and re-purchase should be studied extensively. This study intends to identify the key drivers that influence the satisfaction and the model which can predict the likelihood of customer satisfaction. The outcome would provide insights to prioritise factors that are significant, as well as to provide advice to a wide range of sellers. Four classification machine learning algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The Results showed that Ada boost achieves the highest accuracy, clustering before prediction improve the prediction accuracy such as Ada Boost accuracy before segmentation was 94% but after segmentation increased to 95% and also found out that cluster I important to analyze because non churn rate was higher compared to cluster II and III customers. Anne-Nee Wong and Booma Poolan Marikannan in [23], highlighted the importance of customer feedback in ecommerce success. They introduced a model that analyzed factors affecting customer satisfaction using four classification algorithms-Random Forest, Support Vector Machine (SVM), Decision Tree, and Artificial Neural Network-applied to a Brazilian E-commerce dataset.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…The Results showed that Ada boost achieves the highest accuracy, clustering before prediction improve the prediction accuracy such as Ada Boost accuracy before segmentation was 94% but after segmentation increased to 95% and also found out that cluster I important to analyze because non churn rate was higher compared to cluster II and III customers. Anne-Nee Wong and Booma Poolan Marikannan in [23], highlighted the importance of customer feedback in ecommerce success. They introduced a model that analyzed factors affecting customer satisfaction using four classification algorithms-Random Forest, Support Vector Machine (SVM), Decision Tree, and Artificial Neural Network-applied to a Brazilian E-commerce dataset.…”
Section: -Literature Reviewmentioning
confidence: 99%